Non-domination, contestation and freedom: The contribution of Philip Pettit to learning and democracy in organisations. Issue 3 (July 2015) - Griffin, Martyn; Learmonth, Mark; Elliott, Carole
This article provides a reading of the civic republican ideas of the political philosopher Philip Pettit in order to make new contributions to learning within organisational life. Our aim is to achieve non-domination in the workplace, and we suggest how Pettit's work, through the provision of a democratic constitution and development of the resources of individuals and groups, might inspire eminently practical ways in which to increase freedom and minimise asymmetries of power at work. Such asymmetries have long been an ingrained feature of organisations, confounding even the most progressive attempts to increase opportunities to learn and act within organisations. We do not, therefore, underestimate the problems involved. Nevertheless, we advance our arguments as new – but practicable – contributions to progressive forms of management learning.